Tradisi Haul Teungku Chiek Dianjong di Gampong Peulanggahan Kecamatan Kutaraja Kota Banda Aceh - Husda, Husaini; Naufal, Muhammad; Hermansyah (Indonesian Journal of Islamic History and Culture, 2025)
This research examines the Haul tradition of Teungku Dianjong in Gampong Peulanggahan, Kutaraja District, Banda Aceh, which has been practiced since the 19th century. The Haul is held twice a year, during the months of Ramadan and Dzulqaidah, based on the consensus of the local community. The purpose of this study is to understand the Haul's implementation process, its impact on the community, and the community's perspective on the tradition. This research employs a descriptive qualitative method, with data collected through observation, interviews, and documentation. The data was analyzed through reduction, verification, and conclusion drawing. The results indicate that the Haul process includes stages such as reciting dhikr, Yasin recitation, pilgrimage, and communal feasts. This tradition has a positive impact on religious outreach and increases the community’s awareness of the afterlife. Additionally, the Haul provides economic benefits by attracting many visitors from outside the area. The Peulanggahan community is highly enthusiastic about this tradition, viewing it as a heritage that brings both spiritual and economic advantages.